Effects of Recreational Activity on Leisure Barriers between Students - Aksoy, Yener; Arslan, Oguzhan (Asian Journal of Education and Training, 2019)
Recreation, which means relaxing and pleasant activities that people do voluntarily in their free time, is a concept that provides the physical and psychological renewal of individuals. The study was conducted on a total of 497 students, 248 men participating in recreational sports activities and 249 men who did not participate in any recreational activities. For this purpose “Leisure Constraints Scale”, which was developed by Alexandris and Carroll (1997) and was conducted in the study of the validity and reliability for Turkish Society by Karaküçük and Gürbüz (2007) was used. Statistical analysis of the study was performed by using SPSS 22,0 package program. The normality hypothesis of the data was analyzed by Kolmogorov-Smirnov test. Since all variables showed normal distribution, parametric tests were applied to the independent variables related to the sub-problems and the leisure time scale subscales. Independent t test was used for paired comparisons and Pearson correlation was used for the relationship between variables. Statistical results were evaluated at 95% confidence interval and p <0.05 significance level. As a result, statistically significant differences were found between the students participating in sportive recreation activity in the field and those who did not participate in any recreational activity in terms of leisure time barriers in terms of Individual Psychology, Social Environment, Service and Transportation, Time, Lack of Friends and Lack of Interest. (p<0, 05).